A review on association of mothers’ Vitamin D deficiency and single nucleotide polymorphism of Vitamin D receptor gene (ApaI) with risk of preterm birth and low birth weight - Dutta, Tinni (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2024.